Native species restoring degraded silvopastoral systems in dry regions - Ouled Belgacem, Azaiez; Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
This blog explores the importance of restoring degraded silvopastoral systems in arid North Africa, specifically Tunisia, where human activities, such as overgrazing and cultivation, coupled with unpredictable weather patterns, have led to severe economic and ecological consequences. To address irreversible degradation, ICARDA, under the CGIAR's Livestock and Climate Initiative, collaborates with national partners and agencies to transform rehabilitation strategies. Previous attempts with non-native species revealed limitations, prompting a shift to well-adapted native species. Challenges associated with exotic varieties include high demand, limited nursery capacity, and inadequate seedling quality. Through webinars and field events, ICARDA emphasizes the value of native species. Despite their slow growth, indigenous species showcase superior adaptability, especially in harsh conditions. Pilot sites in Zaghouan and Beni Khedeche demonstrate successful reseeding and tree planting. Future efforts focus on overcoming seed quantity and quality issues, establishing pilot nurseries, promoting non-conventional water use, and fostering Public-Private Partnerships for sustainable restoration.